JAVMA News (Journal of the American Veterinary Medical Association, 2013)
Owner noncompliance, not preventive failure, drives most canine Dirofilaria immitis infections in established patients. Only 24.4% of dogs under care achieve full-year purchase compliance with monthly macrocyclic lactones. Informal data suggest far more practices send annual testing reminders than monthly dosing reminders. The primary goal is continuous chemical protection, not annual detection of prior failures. This viewpoint argues for tracking adherence rates, routine adherence counseling, and prospective evaluation of adherence-first protocols in standard prescription-renewal settings.